Seasonal Variations of Some Physicochemical Parameters of the Brackish Water Farm, Buguma, Niger Delta, Nigeria - Kingsley, Owhonda, Ndubuisi (Recent Research Advances in Biology Vol. 8, 2021)
The Nigerian Institute for Oceanography and Marine Research/African Regional Aquaculture Centre (NIOMR/ARAC) brackish water fish farm, Buguma is an example of tidal water between the farm and adjoining creek, where tidal water flows into the farm and out, enhancing constant exchange of water. Water quality parameter reflects the water composition as affected by both natural and anthropogenic activities expressed in terms of measurable quantities. Knowledge of hydrological conditions of water body helps assess its productivity as well as a better understanding of the population and life cycle of the fish community. The result obtained indicates that for 2011 pH; ammonia-nitrogen; nitrite-nitrogen; nitrate-nitrogen; alkalinity; carbon (iv) oxide; salinity; dissolved oxygen and temperature ranges were between 6.5-7; 0-0.1 ppm; 0.25-0.25 ppm; 40-80 ppm; 5-10 ppm; 9-20 ppt; 3.8-6 ppm and 26-31°C respectively while for 2012 pH; ammonia-nitrogen; nitritenitrogen; nitrate-nitrogen; alkalinity; carbon (iv) oxide; salinity; dissolved oxygen and temperature ranges were between 6.5-7; 0-0.1 ppm; 0.05-0.05 ppm; 0.05-0.25 ppm; 40-80 ppm; 5-10 ppm; 9-20 ppm; 3.8-5.6 ppm; 26-31oC respectively. There were no significant differences (p>0.05) in all parameters for both years and the values measured were within tolerable limits for optimum aquaculture. proper management of these parameters will contribute immensely to fish production and enhance experiments seeking to adapt fish species to this region in the Niger Delta when tolerable limits has been established.